(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The linguistic complexity of multilingual countries presents many questions in developing a discussion about learning and teaching style and curriculum planning that facilitate the learning process for multilingual learners. This research will examine the complexities of Foreign Language Acquisition (FLA) by questioning the benefits of translanguaging theory developed by Baker, García and Li Wei, in order to facilitate the interplay between different languages in the classroom and allow learners to employ their full linguistic repertoires. The present paper will examine the origins and development of translanguaging in the multilingual classroom as a pedagogical practice, working with the interdependence of two (or more) languages that enables learners’ linguistic and cognitive capabilities. The paper will be divided into three parts. The first one will analyse the origins of the term and its development as pedagogical theory. The second part of the paper will focus on the positive effect of using translanguaging in the foreign language classroom. Finally, the third part of the paper will consider the improvements that the foreign language education settings should embrace while adopting translanguaging as a pedagogical practice.